The Synthesis, Structure and Magnetic Properties of O-Vanillin-Derived Schiff Base Polynuclear Lanthanide Single-Molecule Magnets - Jiang, Yu Ting (Université d'Ottawa / University of Ottawa, 2015)
This thesis describes the synthesis, characterization and magnetic investigation of homometallic lanthanide complexes based on two different o-vanillin-derived Schiff base ligands: H2ovph and H2ovgrd. The studies were performed using single crystal X-ray diffractometry, Powder XRD and SQUID magnetometry. Chapter 2 focuses on dinuclear systems 1-8 coordinated to the ligand H2ovph and presents their structural and magnetic properties, mainly with respect to their intramolecular interactions. Chapter 3 describes two hexanuclear systems, 9 (DyIII) and 10 (GdIII), with trigonal prism-assembled core structures. A structural comparison to other similar complexes in the literature is performed. A series of dinuclear complexes, 11-15, based on the ligand H2ovgrd are described in Chapter 4, focusing on the synthetic strategy, crystal structures and magnetism. The presence of the lanthanide contraction is evident in this system of complexes and is consistent with the intrinsic lanthanide contraction property.
Keywords: Single-Molecule Magnets; Lanthanides; O-vanillin-derived Schiff base